(untitled) (Altre Modernità, 2022)
The covid-19 pandemic has had an impact on all aspects of individuals’ lives, including how they interact and strenghthen relations with others. Language, as an essential communication tool, has also been affected by the new situation and, exceptionally quickly, speakers and institutions have incorporated new terms and given new meanings to existing words. On the other hand, experts -linguists, academics, journalists- express their opinions on these linguistic developments and, in doing so, they show their own attitude towards language. This paper studies the echo that the words related to covid-19 have had in the Spanish media and analyzes, from a critical perspective, the reception of the new terms related to the pandemic, the ideological position taken by experts, and the degrees of linguistic and social purism that they manifest towards these words. The analysis has been carried out on a corpus of columns about language (CSL) published between March 2020 and April 2021 in the Spanish press. The analysis of such metalinguistic texts allows the researcher not only collecting an important part of the emerging vocabulary, but also identifying the position taken by linguists, journalistas and general observers of language change within a linguistic community.